An evaluation of the impact of performing arts on the knowledge of Tuberculosis and Clinical Research in adolescents in selected high schools in the Boland Overberg region, Western Cape - De Kock, Marwou (Department of Paediatrics and Child Health, 2016)
Background: There is a high incidence of Mycobacterium tuberculosis (M tb) infection and active Tuberculosis (TB) disease among adolescents in high TB burden countries, such as South Africa (SA), which indicates that clinical trials assessing vaccine-induced protection are critical in this age group. In educating adolescents regarding TB and clinical trials it is important to ensure that this population has received some relevant prior information if they are approached for clinical research, as well as for the benefits to their own health. Method: Applied theatre was used to educate and inform adolescents to improve their knowledge about TB and clinical research. The script used was based on a young mother's decision to enroll her baby as a participant in a TB vaccine trial and the questions asked by her family and the community. The story played itself out in public transport, a local clinic and the participants' household, using singing, dancing and rap in the local dialect. The message was visually delivered by actors from the Worcester Senior Secondary (WSS) School's drama class in an adolescent-friendly format to learners. A pre-performance multiple choice knowledge survey was completed by the study population before they watched the play and approximately seven days after the play the same knowledge survey was completed as a post-test. Results: Of the total study population 4.56% of the adolescents had had TB previously and 39.15 % had been involved in TB research. A high number of the adolescents (97. 7 0 %) had heard about TB and 78. 39 % indicated that they heard about TB at school. The majority of adolescents knew that TB is contagious: 82.92 % in pre-and 97.26 % in post-test. The results for mode of prevention (covering your mouth when coughing / sneezing) in the pre-test for all the schools were above 9 1.28 %. In all tested schools combined there was a slight knowledge increase from pre-to post-test that TB is curable. There was a significant knowledge improvement (P=0.009) for the question: "TB can easily be cured if you take your treatment?" Reassuringly, 9 4.84 % (pre-test) and 9 2.78 % (post-test) indicated that they would consult a medical doctor or go to the clinic if they thought they had TB. Clinical research knowledge did not improve. Conclusion: Using applied theatre to sensitize a rural adolescent population to TB-related clinical research was a novel approach to educate and convey sensitive information to potential study participants. Through theatre, SATVI raised awareness and established strong partnerships with the Department of Basic Education (DoE), school principals, teachers and adolescents as well as indirectly with their parents. It created a platform to engage with the adolescents as well as sensitizing them for a future clinical trial.